A Minimalist Account of Structural Case Assignment in Pashto Conjoined Subject Constructions - Masood, Talat; Rahman, Mujib (The Journal of Humanities & Social Sciences, 2023)
Whereas cross-linguistically the verb of a conjoined subject either agrees with the first of the two conjuncts, called first conjunct agreement (FCA) or with the second conjunct, called second conjunct agreement (SCA) or last conjunct agreement (LCA), Pashto ao conjoined subjects are different in the sense that the verb shows agreement neither with the first conjunct nor the last conjunct. Rather, it shows agreement with the joint syntactic and semantic effect of the two conjoined subjects. Morphologically, in the present and future tenses, ao conjoined subjects show nominative Cases, while in the past tense they show accusative Cases. We propose, for Pashto ao conjoined subjects, following the minimalist idea of agreement in terms of features as responsible for structural Case assignment, that a single agree relation establishes between the conjoined subjects and T in the present and future tenses and between the conjoined subjects and Voice in the past tense. Agreement between T and ao conjoined subjects results in assigning nominative Case while agreement between Voice and ao conjoined subjects results in assigning accusative Case, as υ in the past tense Pashto constructions, we consider, to be defective in the Chomskian sense (2001). The overall conclusion, for structural Case assignment in Pashto ao conjoined subjects constructions, is that the minimalist idea of structural Case assignment as a result of features agreement between a functional head and a nominal hold equally good.